Inducing puberty in beef heifers with hormones - R. DeBenedetti; G.H. Kiracofe; V. Hultine; R.M. McKee; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1976)
Twenty-six Polled Hereford and Simmental-cross heifers that had not cycled by the beginning of the breeding season were given an ear implant and injected with an estrogen-progestogen compound. The implant was removed after 9 days and all heifers were in estrus 1 to 5 days later. Six heifers conceived the first insemination, 11 the second, and 24 during the 65-day breeding season.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Hormones; Implant; Synchronize